Perancangan Hotel Bintang Empat di Kota Tarakan Kalimantan Utara dengan Pendekatan Arsitektur Neo Vernakular - Rizaldi Bilhaq Firdaus; Widi Cahya Yudhanta (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Tarakan City, as the largest city in North Kalimantan Province, plays a strategic role as a center for economics, trade, and tourism. Good accessibility through its international airport and seaport makes Tarakan a major gateway to various destinations in North Kalimantan. This potential is supported by its rich natural resources and cultural heritage, as well as its position as a distribution hub for goods and services. However, the development of the tourism sector remains hampered by the limited availability of premium accommodation facilities that meet international standards, particularly for domestic and international tourists, as well as business travelers. This final project proposes the design of a four-star hotel in Tarakan City as a solution to increase the attractiveness and competitiveness of the tourism sector. The concept used is Neo-Vernacular Architecture, a design approach that combines traditional architectural values with modern needs and technology. This concept aims to maintain local identity, enrich the building's aesthetic qualities, and create comfortable spaces suited to the local tropical climate. During the design process, a thorough analysis of site conditions, climate characteristics, local cultural potential, and four-star hotel operational standards was conducted. The traditional architecture of the Baloy Mayo traditional house served as the primary inspiration, both in terms of form, decorative elements, and spatial philosophy, resulting in a design that is contextual and representative of Tidung culture as one of Tarakan's identities. The resulting design is expected to provide quality accommodation facilities that not only support the needs of tourists and business people, but also become a modern architectural icon that respects and preserves local culture. The presence of this hotel is expected to contribute to the development of the tourism industry and strengthen the image of Tarakan City as a leading destination in North Kalimantan.